Rapid screening of creep resistance in additive manufactured Ti-6Al-4V alloy - Pellicotte, Jacob; Hossain, Md Abir; Egan, Ashton J.; Mills, Michael J.; Stewart, Calvin M. (Materials Science and Engineering A-Structural Materials Properties Microstructure and Processing, 2024)
In this study, rapid screening of creep resistance for additively manufactured (AM) materials is enabled using an accelerated creep test (ACT) called the dynamic negative stepped test (DNST). Additively manufactured components are on the rise in aerospace systems, particularly turbine engine parts. It can be challenging to identify the AM process parameters that correspond to high-temperature strength and creep resistance. Tests are needed that rapidly screen and qualify creep resistance. In DNST, the temperature is held constant, and the specimen is taken through a series of load holds from high to low. The DNST contains two distinct characteristics: (1) the hold duration for each step is “dynamically” controlled to ensure the minimum-creep-strain-rate is achieved at every step, and (2) the “descending” profile maximizes damage accumulation while remaining on the edge of instability. The DNST assesses a material's ability to resist creep damage accumulated across multiple deformation mechanisms. In this study, electron beam melted Ti–6Al–4V, built at six (6) directions: 0°, 30°, 45°, 60°, 90°, and V, is tested using a four-step DNST at 650 °C. Analysis of the minimum-creep-strain-rate (at each step), creep ductility, and rupture were performed. A strain energy density (SED) benchmark metric was established to rapidly screen and classify creep resistance using an “Ashby-like” plot that balanced energy dissipated and energy dissipation rate. The creep resistance was found to be ranked from V, 60, 45, 30, 90, and 0 in descending order. Microstructural and crystallographic characterization revealed grain refinement progressing from the strain-free to the high-strain regions, indicative of dynamic recrystallization (DRX). Further observations revealed that the material's energy capacity increased with the alignment of the grains' long axis and tensile direction.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Accelerated testing; Additive manufacturing; Creep mechanisms; Electron beam melting; Strain energy density